CONDITIONS OF FORMATION OF THE AKCHATAU TOPAZ-BEARING BIOTITE-ALBITE GRANITE - Reyf F.G.; Serykh V.I.; Kanakin S.V. (My University, 1989)
After the well-known work by V.I. Kovalenko and N.I. Kovalenko demonstrating the reality of crystallization of topaz from granitic melts rich in fluorine, the number of new finds of ongonite-like rocks increased steadily. However, the magmatic origin of the topaz in granites has not been completely established in all cases, and data on the range of PTX conditions of formation of these special rocks remain fragmentary. A thermobarogeochemical study of topaz-bearing granite from a new locality (in Central Kazakhstan) has made it possible to determine the composition of melt inclusions in topaz for the first time and to estimate the PT conditions under which these rocks have crystallized.